Visión achual del paraíso - Gómez Navarro, Héctor (2021)
This article shows a translation and analysis of the Native Peruvian’s myths. The texts talk about the loss of the endemic condition and the origin of Achual´s people and institutions. The analysis and study try to provide a philological and anthropological look about these myths.